Can benign lymphoid tissue changes in 18F-FDG PET/CT predict response to immunotherapy in metastatic melanoma? - Sachpekidis, Christos; Larribere, Lionel; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (Cancer immunology immunotherapy, 2018)
BackgroundAn association between immune-related adverse events (irAEs) caused by immunotherapeutic agents and the clinical benefit of immunotherapy has been suggested. We retrospectively evaluated by means of 18F-FDG PET/CT lymphoid tissue changes in the mediastinal/hilar lymph nodes and the spleen in response to ipilimumab administration in metastatic melanoma.MethodsA total of 41 patients with unresectable metastatic melanoma underwent 18F-FDG PET/CT before the start of ipilimumab (baseline PET/CT), after two cycles (interim PET/CT) and at the end of treatment (late PET/CT). Data analysis was focused on the mediastinal/hilar lymph nodes and the spleen. The patients’ best clinical response (BCR) was used as reference.ResultsAccording to the BCR reference, 31 patients showed disease control (DC) and 10 patients showed progressive disease (PD). Mediastinal/hilar lymph node evaluation revealed that in total 4 patients in the interim or late PET/CT (10%) demonstrated a ‘sarcoid-like lymphadenopathy’ as response to treatment (LN-positive). All LN-positive patients responded to ipilimumab with DC. On the other hand, no significant differences between the DC and PD groups regarding both semi-quantitative and quantitative 18F-FDG PET spleen-related parameters at baseline and as response to treatment were detected.ConclusionBased on our findings, 10% patients in the interim or late PET/CT showed ‘sarcoid-like lymphadenopathy’ as response to treatment. All these patients showed disease control, implying a relation between the appearance of sarcoid-like lymphadenopathy and the clinical benefit of anti-CTLA-4 therapy. On the other hand, quantitative 18F-FDG PET analysis of the spleen showed a poor performance in predicting clinical benefit to ipilimumab.
Im Titel ist "18" in 18F-FDG PET/CT hochgestellt
Gesehen am 10.05.2019